Analysis af Thermal Overload Relay (TOR) as a Protection Component For 3-Phase Induction Motors in Plastic Seed Chopping Machines - Mhd. Ali Akbar Nasution; Solly Aryza; Ahmad Dani (Sean Institute, 2025)
Three-phase induction motors require a protection system to safeguard them from various electrical threats, such as overvoltage, overload, and short circuits. This study analyzes a protection system used in a plastic seed chopping machine, where a thermal overload relay (TOR) is implemented as an overload protection mechanism. The TOR functions as a load controller to prevent the motor from overheating and burning out during operation. Based on the analysis, the following results were obtained: Premium Efficiency 3-Phase Induction Motor HLS447SR0608 operates with a nominal current of 6.2 A. The appropriate TOR setting is determined by multiplying the nominal current by 120%, resulting in a setting of 7.4 A.Induction Motor Aeef Frame 112m 3 Phase operates at 5.9 A, requiring a TOR setting of 7.08 A. Siemens P21 Plus Efficiency Motor 3 Phase 1LA02864SE41 operates at 4.5 A, with an appropriate TOR setting of 5.4 A. Three Phase Cage Induction Motor ACI-225M-8 operates at 5.5 A, requiring a TOR setting of 6.6 A. These findings demonstrate that using a TOR as a protection component effectively prevents motor damage due to overload, ensuring the safe and efficient operation of three-phase induction motors in plastic seed chopping machines.